Mercado secundário de títulos públicos: microestrutura, liquidez e spread de compra e venda para o mercado de LTNs no Brasil - Sá Júnior, Euridson de (2007)
This work comprises two parts. First part, it discusses and compares liquidity and market microstructure aspects from government securities in some countries as Brazil, Chile, Mexico, Korea, Poland and United States. The analyses uses some microstructure dimensions like the liquidity from secondary market (bid and ask spread, turnover to average outstanding stock and most important maturity), the efficiency costs, infrastructure and transparency from primary and secondary market and the market security. The goal is to describe the microstructure of secondary markets from theses countries and to compare with the microstructure of Brazilian secondary markets. Despite of low tenor from government securities the Brazilian secondary market presents microstructure like those countries that suggested other reasons avoiding enlarge tenors from prefixed securities. The second part of this work examines the liquidity of the local secondary market for the Brazilian government securities between 2003 to 2006 and the determinants of realized bid-ask spreads for secondary market of the LTNs – Letras do Tesouro Nacional between 2005 to 2006. The spreads were calculated from daily basis with high frequency database for 30 minutes period and one-day period. Overall, the liquidity is an important determinant of the realized bid-ask spread for the LTN market. Specifically, the bid-ask spread decreases when the volume increases. The bid-ask spread increases in the remaining-time-to-maturity of LTN. LTNs up to 30 days tenor presented average bid-ask spreads around 1 cents of reais (1.89 bp) and LTNs with two years tenor presented average bid-ask spreads around 54 cents of reais (3.84 bp) for 30 minutes period and 81 cents of reais (5.72 bp) for one day period. The econometric tests were performed based on a model presented by Chakravarty e Sarkar (1999) applied to USA bonds markets for the years 1995 to 1997. The tests were estimated by Generalized Method of Moments (GMM) technique. Our estimation and evaluation of liquidity measures for the Brazilian government securities market reveal that the simple bid-ask spread is a useful measure for assessing and tracking liquidity.